How does the perceived green human resource management impact employee’s green innovative behavior? —From the perspective of theory of planned behavior - Song, Dian; Bai, Yan; Wu, Hainan; Wang, Xiaoyuan (Frontiers in Psychology, 2023)
Employees’ green innovative behavior encouraged by enterprises plays an important role in the enterprise sustainable development. The study explores the impact of perceived green human resource management on employees’ innovative behavior. Drawing upon the planned behavior theory, this study examines how perceived green human resource management impact employees’ green innovation behavior. Through three-stage questionnaire survey, 207 samples are obtained and hierarchical regression is employed to test the hypothesis., Data analysis results show that perceived green human resource management has a directly positive effect on employees’ green innovative behavior. Green behavior intention, self-efficacy of environmental protection behavior, and identity with the company’s green environmental protection system are the mediators between perceived green human resource management and employees’ green innovative behavior. Meanwhile, the results demonstrate that there is a chain mediating relationship among these variables. In addition, green supply chain management moderates the relationship between the identity of a green environmental protection system and employees’ green innovative behavior. These conclusions transcend the macro perspective and open the black box between green human resource management and enterprise performance. Enterprise should take a holistic view to play the role of green human resource management and supply chain management in the implementation of environmental strategy.